Mullah Khalil Al-Sirti in his book (Al kafiyal kobra in grammar) A study in the author and author - شوکت عارف محمد; عزالدین حسن جمیل الاتروشی (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This research sheds light on the scientific personality of Mullah Khalil bin Hussain bin Omar al-Hayazani Al-Sirati al-Shafi'i (1167-1259 AH), who served his Islamic nation with the scientific effects he has left on the face of eternity. And he grew up in the arms of the Kurdish school before the end of the Ottoman rule by almost a century. He was taken from the schools of the district of Wan to the schools of Diyarbakir, and he did not stop. In one school and not in one world, but in the schools of the mullahs We decided to shed light on Mulla Khalil Al-Sirati in his book "The Great Adequacy in Grammar", a study of the author and the author. The research included two topics and a conclusion. The second topic is devoted to talking about the approach of Mullah Khalil Al-Sirty in his book Al-Kafimah Al-Kubra, and divided into four demands: addressing the first requirement: the sections of the word, the characteristics of the name, its classes, and the sections of science. , And types of expressions, and the second requirement: was to talk about And the third requirement: it was specific to the defamation, and its conditions, and the fourth and final requirement: we talked about the missing acts, acts of praise and slander, and the characters already distorted. Finally, we would like to say that this research is a modest contribution by us to show the efforts of a Muslim scholar of the Kurds. It is a work that we ask God Almighty for loyalty and acceptance and to write to your scientific conference every success and success. Thank God Almighty for making this work in the balance of our good deeds.